(untitled) (Patan Pragya, 2019)
Migration is a never ending issue in the world. This change of thinking about migration is drawn from the understanding that migration, if well managed, may generate important gains for both the host countries and the migrants’ countries of origin. Indeed, there is by now a growing consensus in policy circles that the management of the accelerating globalization process – including effective domestic adjustment posed by it necessitates a coherent approach to policymaking as well as increased co-operation with global partners. Gains tend to become more diffused within sending countries when labour markets are integrated; segmentation, either due to inadequate infrastructure or cultural and ethnic barriers, can restrict gains within migrant communities and might increase relative deprivation of non- migrant ones. However, there exist cases are inequality -depending on which group the migrants are labour depletion. Moreover, migration may have both positive and negative social effects in terms of children’s education and health depending on changes in family composition and the role of women within the family and society. Remittance flows do benefit both the migrants’ households and the non recipient ones through multiplier effects of spending.